Endovascular treatment of a small infrarenal abdominal aortic aneurysm causing duodenal obstruction: Case report and literature review. (June 2015) - Esposito, Andrea; Menna, Danilo; Mansour, Wassim; Sirignano, Pasqualino; Capoccia, Laura; Speziale, Francesco
Duodenal obstruction caused by abdominal aortic aneurysm was first described by Osler in 1905 and is named "aortoduodenal syndrome." This condition has always been treated by open surgical repair. We report the first case of aortoduodenal syndrome successfully treated by endovascular aneurysm repair. A 74-year-old male patient referred to our hospital complaining postprandial vomit, reporting a consistent weight loss in the latest weeks. Enhanced computed tomography scans showed a small saccular abdominal aortic aneurysm compressing duodenum and inferior vena cava without any other evident pathological finding. As the patient underwent a successful endovascular treatment of the abdominal aortic aneurysm, symptoms immediately resolved so that he started back to feed and progressively gained body weight. Despite aortoduodenal syndrome is generally caused by large abdominal aortic aneurysm, this condition has to be suspected also in case of small abdominal aortic aneurysm. Differently from what has been reported in literature, endovascular aneurysm repair could be effective in the treatment of aortoduodenal syndrome.